2018
DOI: 10.1002/2017jd027364
|View full text |Cite
|
Sign up to set email alerts
|

Siting Background Towers to Characterize Incoming Air for Urban Greenhouse Gas Estimation: A Case Study in the Washington, DC/Baltimore Area

Abstract: There is increased interest in understanding urban greenhouse gas (GHG) emissions. To accurately estimate city emissions, the influence of extraurban fluxes must first be removed from urban greenhouse gas (GHG) observations. This is especially true for regions, such as the U.S. Northeastern Corridor‐Baltimore/Washington, DC (NEC‐B/W), downwind of large fluxes. To help site background towers for the NEC‐B/W, we use a coupled Bayesian Information Criteria and geostatistical regression approach to help site four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
(55 reference statements)
5
39
2
Order By: Relevance
“…In the temperate latitudes the CO 2 uptake of plants usually predominates in spring and summer. A modelling study using synthetic CO 2 data by Mueller et al (2018) showed, that for the Baltimore-Washington area a substantial fraction of ~3 5% of the CO 2 background variability is caused by biogenic sources and sinks in July. Therefore, we simulate the biogenic CO 2 flux with the Vegetation Photosynthesis and Respiration Model (VPRM, Mahadevan et al, 2008) coupled with WRF-GHG (Beck et al, 2013) in order to estimate the influence of the photosynthetic uptake and respiration on our assessment of the anthropogenic flux.…”
Section: Discussion On Emission Fluxesmentioning
confidence: 99%
“…In the temperate latitudes the CO 2 uptake of plants usually predominates in spring and summer. A modelling study using synthetic CO 2 data by Mueller et al (2018) showed, that for the Baltimore-Washington area a substantial fraction of ~3 5% of the CO 2 background variability is caused by biogenic sources and sinks in July. Therefore, we simulate the biogenic CO 2 flux with the Vegetation Photosynthesis and Respiration Model (VPRM, Mahadevan et al, 2008) coupled with WRF-GHG (Beck et al, 2013) in order to estimate the influence of the photosynthetic uptake and respiration on our assessment of the anthropogenic flux.…”
Section: Discussion On Emission Fluxesmentioning
confidence: 99%
“…Sixteen of these station locations were chosen to be used for emissions estimation in a domain around Baltimore and Washington, D.C. (red boundary, Fig. 1) using inverse modelling techniques (Lopez-Coto et al, 2017;Mueller et al, 2018). Three others are in Mashpee, MA, Philadelphia, PA, and Waterford Works, NJ.…”
Section: Network Design and Site Characterizationmentioning
confidence: 99%
“…A second design study determined ideal 100 locations for background stations, i.e. observation station locations that would aid in the determination of background CO2 entering the analysis domain (Mueller et al, 2018). Four stations were identified as part of that study; an existing EN site in Bucktown, MD, serves as a fifth background station southeast of the analysis domain ( Fig.…”
mentioning
confidence: 99%
“…In contrast, atmospheric carbon concentrations measured from surface stations or satellite sensors, together with inverse modeling (e.g., Hybrid Single-Particle Lagrangian Integrated Trajectory model by Stein et al, 2015), offer an alternative approach to evaluate carbon inventories and detect trends attributable to policy, regulation, or economic changes (Sargent et al, 2018;Stein et al, 2015). As such, carbon monitoring projects to build observational networks were initiated in many large cities such as Los Angeles (Feng et al, 2016), Salt Lake City (McKain et al, 2012), Paris (Bréon et al, 2015), Portland, Oregon (Rice & Bostrom, 2011), Boston (McKain et al, 2015, Indianapolis , and Washington, DC/Baltimore (Mueller et al, 2018). Their study highlighted the necessity to build multiple network stations in urban areas to monitor surface GHG concentrations in both spatial and temporal domains.…”
Section: Introductionmentioning
confidence: 99%
“…Their study highlighted the necessity to build multiple network stations in urban areas to monitor surface GHG concentrations in both spatial and temporal domains. As such, carbon monitoring projects to build observational networks were initiated in many large cities such as Los Angeles (Feng et al, 2016), Salt Lake City (McKain et al, 2012), Paris (Bréon et al, 2015), Portland, Oregon (Rice & Bostrom, 2011), Boston (McKain et al, 2015, Indianapolis , and Washington, DC/Baltimore (Mueller et al, 2018).…”
Section: Introductionmentioning
confidence: 99%